Pengaruh Penyesuaian Diri Terhadap Stres Akademik pada Mahasiswa FKM Undana Kupang Selama Masa Pandemi Covid-19 di Tahun 2022 - Datu K. Tandirura; Serlie K. A. Littik; Diana Aipipidely (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study aims to determine the effect of adjustment to academic stress on students of the Faculty of Public Health, University of Nusa Cendana Kupang, during the Covid-19 pandemic in 2022. The participants in this study were 400 students of the Faculty of Public Health, University of Nusa Cendana Kupang, for the 2021/2022 academic year. People were selected using a simple random sampling technique. This study uses a quantitative approach with a scale of student adjustment during Rovika's online learning in 2021 and Affani's academic stress scale during online learning in 2021, adapted from Bedewy & Gabriel's (2015) academic stress scale. Data analysis used a simple linear regression test. The results showed that there was a positive influence between adjustment and academic stress (p-value = 0.000; RÂ² = 0.198), where adjustment contributed 19.6% to academic stress experienced by students of the Faculty of Public Health, University of Nusa Cendana Kupang for the 2021/2022 academic year. The higher the perceived academic stress, the better adjustment process is needed for each student during academic learning during the Covid-19 pandemic in 2022.